Islamic Values in the Annual Reports of the Shariah Bank to Create a Sharia Value-Added - Rediyanto Putra; Rahma Rina Wijayanti (Universitas Muhammadiyah Yogyakarta, Indonesia, 2020)
Research Aims: This study aims to examine, understand, and prove the embodiment of Islamic values in the annual report of Sharia Banks. The results of this study are expected to provide information or data to all parties regarding the layout and Islamic values in the Sharia Banks' annual report, which can be a form of a real differentiator between Sharia Banks and conventional banks if viewed in terms of the content of the annual report.Design/Methodology/Approach: The interpretive method in this study is suitable for research purposes that are not intended to perform hypothesis testing but to do an interpretation of research data. The interpretive method used in this research is to analyze the data by using semiotic analysis. Differential semiotic analysis is an analysis of data that focuses on meaning and sign. Semiotic analysis of the annual sharia bank report is carried out on the narrative texts on the annual report. Semiotic analysis in this study is based on Charles Sanders Pierce's semiotic analysis which uses the triangles of meaning.Research findings: The results of the study showed that the annual reports of Muamalat Bank from 2012 to 2016 had indicated Islamic values. Islamic values were found most frequently in the annual report of Muamalat Bank from 2014 to 2016. The Islamic values in the annual reports of Muamalat Bank were included in the Sharia Supervisory Board Report, the Board of Commissioner Report, the Board of Directors, corporate governance information, and information related to Corporate Social Responsibility (CSR). Thus, the presence of Islamic values in the annual reports of Muamalat Bank can create the sharia value added to the company.Theoretical contribution/Originality: The results of this study have contributed to the application of the Shari'ah Enterprise Theory (SET) theory. The existence of the application of Islamic values in the financial statements of Bank Muamalat shows that Bank Muamalat is not only responsible for its business activities to humans (investors) but also to God.Practitioner/Policy implication: The results of this study indicate that Bank Muamalat must continue to maintain the existence of Islamic values in operational activities that are presented in its annual report. This is due to the fact that Bank Muamalat's operational activities are truly in accordance with Islamic law.Research limitation/Implication: The Islamic values were found most frequently in the annual reports of Muamalat Bank from 2014 to 2016. A good practice of Islamic values is finally expected to result in the meaningful added value of sharia. The limitations in this article that are the number of the theory and methodologies related to the phenomenon of Islamic values on the disclosure of information in the annual reports is still limited. So, further researches will be necessary to find another theory and develop methodologies to investigate the Islamic values represented in the annual report of sharia banking.